Is Reduction Mammoplasty Cost-Effective? A Cost-Utility Analysis of Surgical Treatment for Macromastia in Germany - Lux, Michael P.; Brendle-Behnisch, Anne; Hack, Carolin; Preuss, Caroline; Arkudas, Andreas; Horch, Raymund E.; Beckmann, Matthias; Jud, Sebastian (Breast Care, 2021)
Background/Aims: Macromastia can cause physical and psychological problems. Conservative treatments such as physiotherapy and painkillers lead to substantial long-term costs, without any proven medical benefit. In contrast, surgical treatment with reduction mammoplasty leads to improvements in nearly all respects. This study analyzed the costs of reduction mammoplasty and calculated an incremental cost-utility ratio for the treatment. Patients and Methods: The data on 76 patients who underwent reduction mammoplasty between 2008 and 2016 were collected using a two-part questionnaire (preoperative and postoperative) as well as the patients' files. Topics examined besides demographic data included physician visits, medical imaging, integrative medical procedures, remedial procedures, rehabilitation and convalescent measures, drug intake, medical aids, exercise activity, and sick leave days before and after surgery. The data were used to calculate costs per year after surgical treatment for symptomatic macromastia. Costs of surgery, including the process of obtaining insurance reimbursement and postoperative complications, were taken into account to calculate the one-time costs of reduction mammoplasty. Results: The patients' quality of life and satisfaction with the breasts improve after surgery. The one-time costs of reduction mammoplasty per patient amount to EUR 5,885, and the annual costs after surgery are EUR 200. The incremental cost-utility ratio for surgical treatments shows a saving of EUR 380 per quality-adjusted life-year (QALY) gained. Conclusions: These results show that reduction mammoplasty is a treatment that not only improves a patient's quality of life but also saves money in the longer term in comparison with expensive and ineffective conservative treatment for macromastia.
CRIS-Team WoS Importer:2021-02-19